2015
DOI: 10.1021/jacs.5b05805
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic Carbene–Copper-Catalyzed Group-, Site-, and Enantioselective Allylic Substitution with a Readily Accessible Propargyl(pinacolato)boron Reagent: Utility in Stereoselective Synthesis and Mechanistic Attributes

Abstract: The first instances of catalytic allylic substitution reactions involving a propargylic nucleophilic component are presented; reactions are facilitated by 5.0 mol % of a catalyst derived from a chiral N-heterocyclic carbene (NHC) and a copper chloride salt. A silyl-containing propargylic organoboron compound, easily prepared in multigram quantities, serves as the reagent. Aryl- and heteroaryl-substituted disubstituted alkenes within allylic phosphates and those with an alkyl or a silyl group can be used. Funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 102 publications
3
69
1
Order By: Relevance
“…3a). The computational errors for modeling a charged species notwithstanding, we propose a similar steric and electronic environment as suggested formerly vis-à-vis enantioselective allylic substitutions effected by the same catalyst class 27 . The sulfonate group is probably situated in the rear ( I – II ); this would allow for the large 3,5-bis-(2,4,6-( i -Pr) 3 -phenyl)phenyl moiety to obstruct the right side of the complex, and causes the sizeable B(pin) moiety to be situated in the less occupied left/front quadrant in I (Fig.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…3a). The computational errors for modeling a charged species notwithstanding, we propose a similar steric and electronic environment as suggested formerly vis-à-vis enantioselective allylic substitutions effected by the same catalyst class 27 . The sulfonate group is probably situated in the rear ( I – II ); this would allow for the large 3,5-bis-(2,4,6-( i -Pr) 3 -phenyl)phenyl moiety to obstruct the right side of the complex, and causes the sizeable B(pin) moiety to be situated in the less occupied left/front quadrant in I (Fig.…”
Section: Resultssupporting
confidence: 62%
“…These investigations provide the first step towards development of a series of catalytic enantioselective reactions involving N-H ketimines and other types of readily available and versatile carbon-based nucleophiles, protocols that render a range of chiral drug candidates with one or more α-tertiary amine moieties much more accessible. Finally, this study further expands the utility of sulfonate-containing chiral NHC ligands, previously utilized in catalytic enantioselective conjugate additions 48 , allylic substitutions 49 as well as copper-boryl additions to alkenes 50 and allenes 51 and copper–hydride additions to alkenes 52 , to include allyl additions to ketimines.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…[46,7] We first found that EAS with only CuCl (no ligand) proceeds to 45% conversion, affording the linear isomer ( 4a ) exclusively (Table 1, entry 1). A chiral ligand would have to bind efficiently to the transition metal and/or the derived Cu complex to promote formation considerably faster than a free Cu complex.…”
mentioning
confidence: 99%
“…[14] As part of our ongoing program towards iridium-catalyzed allylic substitution reactions, [15] we envisaged that chiral NHCs would be promising ligands for iridium and the corresponding Ir/NHC complexes might be efficient catalysts in allylic substitution reactions. Herein, we report the first example of using an iridium(I) N-heterocyclic carbene complex as the catalyst for the highly enantioselective intramolecular allylic amination reaction of indoles and pyrroles.…”
mentioning
confidence: 99%